Analisis Faktor Penghambat dan Upaya Peningkatan Literasi pada Siswa Kelas 1 di SDN Pabean Kabupaten Probolinggo - ., Ryzca Siti Qomariyah; ., Ajunaida Kurniawati; ., Farihah Zamili; ., Adenita Faradilla (CV. ITTC INDONESIA, 2022)
Currently reading literacy in Indonesia is very low, due to a lack of interest in reading. This has happened since childhood, we are not used to reading. Reading literacy is the ability to understand in the form of written language needed by society. Mastery of literacy is important for increasing the achievements of the millennial generation in achieving success. Literacy cultivation must be carried out early on and realized because it is the main capital in creating an intelligent nation. Literacy activities are really needed for students to improve their reading quality. However, it is very unfortunate, when the Covid-19 pandemic hit Indonesia, it resulted in a decrease in the quality of children's literacy, especially at the Kindergarten level who will enter Elementary School. The method of this research is in the form of interviews and observations of grade 1 elementary school teachers, namely by increasing the reading and writing literacy culture movement for grade 1 students of SD Pabean Probolinggo. Based on the results of the interviews and observations that we conducted, it was stated that of the 29 students, there were 8 students who could read and 22 students who could not read. Where this shows that, the level of students' writing ability is higher than reading ability.